Enrofloxacin Behavior in Presence of Soil Extracted Organic Matter: An Electrochemical Approach - Escudey-Castro, A; Escudey-Castro, A (Elsevier Ltd, 2017)
In this work, a novel and simple method aimed at determining and quantifying Enrofloxacin in presence of Natural Organic Matter (NOM) is proposed. The method was based on the electrochemical oxidation of Enrofloxacin by using cyclic voltammetry as technique. It was found that this analyte presents a good electroactivity, in absence and in presence of NOM. However, this electrochemical behavior is highly pH-dependent, since the reaction is more favorable when less acid the media is. At this point, different pH values were studied in order to corroborate this phenomenon. Additionally, kinetic studies were done to determine the control of the reaction, the number of transferred electrons in the entire process and the rate determining step of the reaction by analyzing the Tafel slope. With these antecedents, a mechanism was proposed and the final product of the reaction was corroborated by using LC-MS. Finally, analytical parameters were studied with the aim of proposing this new method as an electrochemical sensor of Enrofloxacin. It was found that the method is highly linear, precise and accurate. Moreover, this method is not only sensitive but also selective to Enrofloxacin in presence of NOM, in comparison to spectrophotometric methods previously reported. © 2017 Elsevier Ltd